Determinants of Health Professionals' Migration in Africa: a WHO based Assessment - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Purpose How do economic prosperity, health expenditure, savings, price-stability, demographic change, democracy, corruption-control, press-freedom, government effectiveness, human development, foreign-aid, physical security, trade openness and financial liberalization play-out in the fight against health-worker crisis when existing emigration levels matter? Despite the acute concern of health-worker crisis in Africa owing to emigration, lack of relevant data has made the subject matter empirically void over the last decades. Design/methodology/approach A quantile regression approach is used to assess the determinants of health-worker emigration throughout the conditional distributions of health-worker emigration. This provides an assessment of the determinants when existing emigrations levels matter. Findings Findings provide a broad range of tools for the fight against health-worker brain-drain. As a policy implication, blanket emigration-control policies are unlikely to succeed equally across countries with different levels of emigration. Thus to be effective, immigration policies should be contingent on the prevailing levels of the crisis and tailored differently across countries with the best and worst records on fighting health worker emigration. Originality/value This paper has examined the theoretical postulations of a WHO report on determinants of health-worker migration.
Keywords: D60; F22; I10; J24; O15; 330; Welfare; Health; Human Capital; Migration; Africa